Polskie i angielskie przekłady Bohatera naszych czasów Michaiła Lermontowa — szkic historyczny - Pisarska, Justyna (Przegląd Rusycystyczny, 2010)
ПОЛЬСКИЕ И АНГЛИЙСКИЕ ПЕРЕВОДЫ РОМАНА ГЕРОЙ НАШЕГО ВРЕМЕНИ МИХАИЛА ЛЕРМОНТОВА — ИСТОРИЧЕСКИЙ ОЧЕРК Резюме Статья представляет собой попытку упорядочить фактографическое знание, а так-же пополнить информации, касающиеся польских и английских переводов романа Михаила Лермонтова Герой нашего времени.Первый польский перевод этого произведения был осуществлен в 1844 году Тео-дором Коеном. Авторами следующих переводов на польский язык являются Лешек Борковский (1848), Чеслав Монковский (1890), Виктор Луборадский (1894), а также Вацлав Рогович (1954).Автором первого английского перевода Героя нашего времени от 1854 года, является Тереса Плушки. Авторы остальных переводов это Р.И. Липман (1886), Джон Свнертон-Филимор (1903), Й.Х. Висдом и Марр Мурей (1912), Реджиналд Мертон (1928), Паул Эден и Паул Цедар (1940), Мартин Паркер (1947), а также Владимир Набоков и Дмитрий Набоков (1958). POLISH AND ENGLISH TRANSLATIONS OF A HERO OF OUR TIME BY MIKHAIL LERMONTOV — A HISTORICAL SKETCH Summary The article presents the attempt to put in order knowledge concerning Polish and English translations of a Hero of Our Time by Mikhail Lermontov. So far there were revealed five Polish and eight English translations of this outstanding novel. The first Polish translation of Герой нашего времени appeared in print in 1844, i.e. only three years after publishing the original novel. Its author was Teodor Köen. The other Polish translations were made by Leszek Borkowski (1848), Czesław Mąkowski (1890), Wiktor Luboradzki (1894) and Wacław Rogowicz (1954).Герой нашего времени was first translated into English language by Theresa Pulszky in 1854. The remaining seven translations were done by R.I. Lipmann (1886), John Swin-nerton-Phillimore (1903), J.H. Wisdom and Marr Murray (1912), Reginald Merton (1928), Paul Eden and Paul Cedar (1940), Martin Parker (1947), Vladimir Nobokov and Dmitri Nabokov (1958).